Characterization and optimization of organoclay- poly(melamine-co-formaldehyde)-methylated solution impregnated pulai (Alstonia spp.) wood using response surface methodology - Perry Law, Nyuk Khui; Md. Rezaur, Rahman; Hafizah, Abdul Halim Yun; Sinin, Hamdan; Muhammad Khusairy, Bakri; Mohammed Mahbubul, Matin; Kuok King, Kuok; Chin Mei, Yun; Abdullah S., Al-Bogami; Khalid A., Alamry; Mohammed ., M. Rahman (NC State University, 2022)
Significant effects of organoclay and poly(melamine-co-formaldehyde)-methylated (PMFM) impregnation on the mechanical, morphological, and thermal characteristics of raw pulai wood were investigated in this work. The material’s modulus of elasticity (MOE) as well as the maximum compression force (MCF) of the impregnated organoclay/PMFM pulai wood samples were optimized using a designed experiment. The MOE and MCF models had R2 values of 0.9228 and 0.8340, respectively. After the impregnation of organoclay/PMFM pulai wood samples, the MOE and MCF increased considerably, indicating that the pulai wood’s mechanical characteristics had improved. The compositional analysis verified the polymerization and dispersion of organoclay and PMFM. Using Fourier transform infrared spectroscopy, reduction in the hydroxyl groups was detected. The impregnated organoclay/PMFM pulai wood samples had successfully filled the pores and cell cavities, as seen by scanning electron microscopy. The thermal stability of the impregnated organoclay/PMFM pulai wood samples was better than that of the raw pulai wood, with a higher glass transition temperature as determined by differential scanning calorimetry. The thermogravimetric study revealed that the impregnated organoclay/PMFM pulai wood samples had higher decomposition temperatures than the raw pulai wood sample.